2003
DOI: 10.1046/j.1526-4610.2003.03103.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Neuromuscular Transmission in Cluster Headache

Abstract: These results suggest that episodic cluster headache may share the same abnormality of neuromuscular transmission observed in migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…36 Another expressive finding is the demonstration of the existence of similar NMT abnormalities in a different type of primary headache syndrome, in cluster type headache as shown by our SFEMG study. 40 We speculate that this finding may also point out to a shared hereditary liability of the trigemino-vascular system and neuromuscular junction for a subclinical and episodic dysfunction. It seems that TGA is a part of this expanded spectrum, with a particular role of the excitatory afferents.…”
Section: Discussionmentioning
confidence: 72%
“…36 Another expressive finding is the demonstration of the existence of similar NMT abnormalities in a different type of primary headache syndrome, in cluster type headache as shown by our SFEMG study. 40 We speculate that this finding may also point out to a shared hereditary liability of the trigemino-vascular system and neuromuscular junction for a subclinical and episodic dysfunction. It seems that TGA is a part of this expanded spectrum, with a particular role of the excitatory afferents.…”
Section: Discussionmentioning
confidence: 72%
“…SFEMG is the most sensitive neurophysiological method of assessing the neuromuscular junction in humans. In our preliminary study, three patients with CH showed prominent NMT abnormality and one further patient had borderline dysfunction of NMT on SFEMG (5). Our SFEMG study compared NMT abnormality in MA and CH patients and found that it was more prominent in CH.…”
Section: Discussionmentioning
confidence: 81%
“…Impairment of neuromuscular transmission (NMT) has been detected by stimulation single-fibre electromyography (SFEMG) in migraine with aura (MA) (1)(2)(3)(4). We have recently reported pronounced abnormalities in NMT by SFEMG in a small group of six patients with episodic cluster headache (ECH), suggesting that CH may share the same abnormality of NMT observed in MA (5).…”
Section: Introductionmentioning
confidence: 99%
“…(57–59, 66) used stimulation SFEMG of EDC, Domitrz et al. (61), Ertas and Baslo (69) and Coban (60) used voluntary EDC contraction SFEMG and Terwindt et al. (62) used stimulation SFEMG of frontalis muscle.…”
Section: Single‐fibre Electromyography a Ambrosini And M Ertasmentioning
confidence: 99%
“…They did not take into account the percentage of abnormal fibres. Ertas and Baslo (69) and Coban (60), who also studied SFEMG during voluntary contraction, considered the test as abnormal if 15% or more MCD values exceeded 55 µs and borderline if 10% of MCD values were above this threshold.…”
Section: Single‐fibre Electromyography a Ambrosini And M Ertasmentioning
confidence: 99%